5.8-GHZ suppressed UWB bandpass filter employing modified CRLH-TL of two and three unit cells - Shen, Yizhu (2013)
This paper presents a novel modified composite right/left-handed (CRLH) unit cell to achieve sharp rejection at 5.8 GHz. Design formulas are theoretically derived and numerically verified. Based on this unit cell, ultra-wideband (UWB) bandpass filters with two and three cells are designed, fabricated, and on-wafer measured. The measurement results show that the CRLH bandpass filter has a rejection of >60 dB at 5.8 GHz, a minimum insertion loss of 1.1 dB, and 3-dB bandwidths of 3.09-4.79 GHz and 3.22-4.61 GHz for the two and three unit cells, respectively.